Mesophyll porosity is modulated by the presence of functional stomata - Marjorie R. Lundgren (Nature Portfolio, 2019)
Gas exchange for photosynthesis occurs via stomata on the leaf surface and the airspace in the underlying mesophyll tissue. Here, the authors show that stomatal function modulates mesophyll airspace formation and that their coordinated development influences water use efficiency in crops